PENGARUH AKUT DIET ATEROGENIK TERHADAP PROFIL LIPID DAN LIPOPROTEIN-PHOSPHOLIPASE A2 - Retno Susilowati (lp2m-uin malang, 2010)
Atherosclerosis is the primary cause of vascular disease is often fatal as coronary heart disease and stroke. The disease is common in chronic and critical stage, this is due partly because the method of early detection of atherosclerotic disease is less effective and clinical symptoms emerged after at this stage even more critical. Atherosclerosis is a chronic disease and occurs in old age, this causes most of atherosclerosis research conducted only on the chronic exposure for 3 months. Therefore needs to be an early marker of atherosclerosis through the observation of the major risk factors of atherosclerosis (lipid profile) in the early exposure (≤ 1 month or less) at a young age. The enzyme Lp-PLA2 is a non-conventional risk factors found in the latest, the activity produces sdLDL with the result also need to be assessed in the presence acute exposure of diet hypercholesterolemic. The research is an experimental research using mice (Mus musculus) aged 2 months with weight on average 200g, divided into two groups namely the control and treatment group of atherogenic diet. Diet treatment was given 4 weeks. At the end of the study, total cholesterol, triglycerides, LDL, HDL and apoB levels to be measured. To find the difference of these parameters, the data are tested using the test T. In addition, related atherogenic diet influence on plasma Lp-PLA2 conducted literature review and descriptive analysis of Lp-PLA2. The results showed that diet affects lipoprotein metabolism characterized by very significance effects (p 0.01) increased levels of total cholesterol, triglycerides, LDL and significantly (p 0.05) lower HDL cholesterol in the blood of mice at exposure for 4 weeks. Atherogenic diet has not shown its impact on apoB levels, which allegedly also had influence on levels of Lp-PLA2 in plasma 4 weeks, but based on literature studies, and levels of Lp-PLA2 activity has increased the exposure of cholesterol and diabetes for a month.